A Review of Technology Innovation in Increasing Rice Production - F. Faisal; Marlina Mustafa; Y. Yusuf (Agrotech Journal, 2019)
Rice is the main commodity in Indonesia so it needs to be supported by technological innovation in the context of increasing production. Currently, the Agricultural Research and Development Agency has created technological innovations to increase rice production because it is necessary to disseminate information on technological innovations so that all users can know and take advantage of these innovations. The purpose of writing this paper is to provide information and an overview of some of the current agricultural technological innovations in Indonesia that contribute to increasing rice production in Indonesia. Several agricultural technology innovations are currently being implemented such as new superior varieties technology, planting jajar legowo, Salibu rice cultivation system, hazton rice cultivation, SRI rice cultivation technology, integrated planting calendar, and integrated crop management. These technological innovations have had an impact on increasing rice production in Indonesia